Thermo-viscoelastic homogenization of 3D woven composites with time-dependent expansion coefficients. (1st June 2022) - Hirsekorn, Martin; Marcin, Lionel; Godon, Thierry
Abstract: Stress relaxation in the viscoelastic matrix influences the evolution of thermal expansion and chemical shrinkage of polymer composites. Its effects are included into a viscoelastic model of the generalized Maxwell type by means of time-dependent thermal expansion and chemical shrinkage coefficients. A homogenization strategy is proposed to obtain these coefficients of the composite from the constituent behaviors, taking into account the viscoelastic effects. The homogenized behavior is validated by full-scale finite element simulations. It reproduces features such as sign changes of the thermal strain rate close to the glass transition temperature and thermal creep effects, which can have an important impact on the residual stress formation in composites, but are not taken into account by classical thermo-elastic homogenization methods. Highlights: Viscoelastic constitutive behavior with time-dependent thermal expansion coefficients. Effect of stress relaxation on the average thermal expansion of a 3D woven composite. Viscoelastic homogenization of thermal expansion and chemical shrinkage coefficients. Validation of the homogenization method by full-scale Finite Element simulations.